Lifetime Duration of Exposure to Biomechanical Factors at Work as a Mediator of the Relationship Between Socioeconomic Position and Walking Speed - d'Errico, Angelo; Ricceri, Fulvio; Descatha, Alexis; Leclerc, Annette; Roquelaure, Yves; Goldberg, Marcel (Frontiers in Public Health, 2020)
Aim of the study was to assess the proportion mediated by duration of exposure to ergonomic factors at work on the relationship between Socioeconomic Position (SEP) and low walking speed. This cross-sectional study was performed on data collected at baseline on 19,704 men and 20,273 women 45-70 years old, currently or previously employed, enrolled in the Constances cohort. SEP was assigned through current or last occupation, categorized in 3 classes, based on the European Socioeconomic Classification. Walking speed was assessed through one measurement of normal walking for 3 meters, and dichotomized at the lowest quintile of the gender and age (5-year) specific distribution. Self-reported workplace exposure throughout working life to repetitive work, intense physical work and lifting/carrying of heavy loads was used to assess duration of exposure to each factor, categorized in four classes. Through Poisson regression models, adjusted for BMI, smoking, alcohol intake, hypertension, physical activity, diabetes, cardiovascular diseases, and a cognitive score, the attenuation in the Prevalence Ratio (PR) of low walking speed by SEP produced by the inclusion of duration of exposure to each factor was evaluated. The mediating effect of work ergonomic exposures on the relationship between SEP and low walking speed was assessed using the Weighted Method by Vanderweele. In the fully adjusted model without ergonomic exposures, both men and women in the middle and the lowest SEP had a significantly increased risk of low walking speed, compared to those in the highest SEP (men: PR=1.30 and PR=1.46, respectively; women: PR=1.24 and PR=1.45, respectively). The inclusion in separate regression models of exposure duration to repetitive work, intense physical work and handling of heavy loads, produced modest risk attenuations in both men and women, all smaller or around 10%. Mediation analysis revealed in both genders significant mediation effects for most ergonomic exposures considered, although also with low mediation effect. Significant different in walking speed by SEP were observed in this large sample, but the proportion of such differences explained by duration of exposure to ergonomic factors at work was low using either the risk attenuation or the mediation analysis methods.